A rare case of disseminated Mycobacterium avium complex with colitis in a renal transplant recipient. Issue 1 (24th October 2018) - Ingilizova, Marinela; Epstein, Shara; Heun Lee, Dong; Patel, Neal; Patel Babariya, Shraddha; Morgenstern, Ricardo; Popnikolov, Nikolay; Coppock, Dagan
Abstract: Mycobacterium avium complex (MAC) colitis is a rare complication of immunosuppression in solid organ transplant (SOT) recipients. Here, we describe a case of disseminated MAC infection with colitis following renal transplantation. Despite common pathways of immunosuppression, SOT recipients and human immunodeficiency virus (HIV)‐infected patients differ in their typical presentations of MAC infection. Intestinal infections have been more commonly reported in HIV‐infected patients than in SOT recipients. The explanation for this difference may be related to HIV's targeted effects on the CD4 + T‐cell reservoir in gut‐associated lymphoid tissue.